Microwave Extraction of Gallic Acid Equivalent of Total Flavonoids from Nigella sativa - Burcu Özturk; Sibel Yiğitarslan (International Journal of Secondary Metabolite)
Unfortunately, cancer is the most widespread disease in worldwide. Colorectal cancer is declared as the third most common cancer type. The usage of controlled-drug-releasing capsules for treating the cancer diseases has becoming more and more popular in the whole world. In the production of drug raw material, the first operation is an extraction of the phytochemicals from the herbal plant. The yield of the extraction operation is an important step for the economical and efficient production of such capsules. Thus the aim of this study was to optimize the microwave extraction of total flavonoids from Nigella sativa with methanol by using Response Surface Methodology based on Box-Behnken design. Microwave extraction experiments had been carried out with the parameters of microwave power, solid/liquid ratio and the and the application time. The optimum values were determined as 0.62 kW, 1/(47) g/mL, and 10.84 second, respectively. According to the quadratic surface of the extraction yield depending on those parameters, 309.60 mg/100g of gallic acid equivalent of total flavonoids can be obtained at the optimum conditions. As a result of the statistical analysis, this function was found as capable of expressing the effect of the parameters on the amount of total flavonoid production in industry. Nowadays, drying of the extracts and loading of the aqueous solutions of them into the prebiotic-coated probiotic capsules have been under consideration.